2018
DOI: 10.1111/ejh.13051
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell lymphomas associated gene expression signature: Bioinformatics analysis based on gene expression Omnibus

Abstract: Our findings uncovered aberrantly expressed genes and a complex RNA signal network in T-cell lymphomas and indicated cancer-related pathways involved in disease initiation and progression, providing a new insight for biotargeted therapy in T-cell lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Previous study reported that the NF-κB pathway, immunosuppressive pathways (TGFβ pathway) and IL-6 signaling were enriched in AITL 18. And Zhou LL et al suggested that activation of PI3K/AKT, JAK-STAT, and NF-κB signaling pathway are associated with processes of T-cell lymphoma 19. These pathways may play an important role in invasion, metastasis, and therapeutic applications for AITL.…”
Section: Discussionmentioning
confidence: 97%
“…Previous study reported that the NF-κB pathway, immunosuppressive pathways (TGFβ pathway) and IL-6 signaling were enriched in AITL 18. And Zhou LL et al suggested that activation of PI3K/AKT, JAK-STAT, and NF-κB signaling pathway are associated with processes of T-cell lymphoma 19. These pathways may play an important role in invasion, metastasis, and therapeutic applications for AITL.…”
Section: Discussionmentioning
confidence: 97%
“…Among those enriched pathways, DGEs included those in the MAPK signaling pathway and PI3K-AKT signaling pathway which have been demonstrated to be associated with chemoresistance, invasion, and metastasis (8)(9)(10). "Pathways in cancer" that regulated the proliferation and apoptosis of cancer cells has been verified (11). KEGG pathway analysis indicated that some of the classic pathways involved in chemoresistance of GC were activated (Figure 3).…”
Section: Go Enrichment Analysis Of Degs a Total Of 1486mentioning
confidence: 96%
“…PDGFRA, CXCL12, and CCL19 were the most significant central genes in the signal-net analysis. in some kinds of lymphomas ( 8 , 11 ).…”
Section: Introductionmentioning
confidence: 99%